Optimization of demand-responsive transit systems using zonal strategy. Issue 3 (3rd July 2018) - Wang, Lin; Wirasinghe, S. C.; Kattan, Lina; Saidi, Saeid
ABSTRACT: A mathematical model was developed and applied to optimize many to one demand-responsive transit (DRT) systems using a zonal strategy. Such a DRT system provides service between a residential area and a terminal. The model is used to design the transit system, with its terminal sitting within the service area, by minimizing costs that are separately generated in service zones. The decision variables are area of service zone and bus headway. Also stepwise procedures are derived to geographically and sequentially divide the service area into a number of service zones with optimal areas. A case study is conducted for a presumptive demand-responsive transit system operating in northwest Calgary, showing that the model can successfully assist in designing demand-responsive transit systems.